THE COMPARISON OF HUMAN RESOURCE MANAGEMENT PRACTICES IN INDONESIAN AND MALAYSIAN COMPANIES - Paeno, Paeno; Ramdani, Dani Taupan (Yayasan Education and Social Center, 2023)
The objective of this study is to conduct a comparative analysis of human resource management (HR) practices implemented in companies based in Indonesia and Malaysia. Human resource management (HRM) is crucial in achieving organizational success. It is subject to the influence of various factors, including cultural dynamics, regulatory frameworks, and distinct business environments that may vary across different countries. Qualitative research methods were used to collect data through interviews with HR managers, field observations, and document analysis. The research results show several significant differences in HR management practices between Indonesian and Malaysian companies. These differences involve recruitment, selection, training, development, compensation, and performance management. Cultural factors, government regulations, and labour market conditions are major determinants of these differences. In addition to these differences, this research also identified several HR management practices that are similar between the two countries, such as an emphasis on employee development and attention to organizational sustainability. The findings of this study contribute to a more comprehensive comprehension of the intricacies involved in human resource management practices in Indonesia and Malaysia, as well as the potential ramifications for forthcoming human resource management policies. The findings above can be utilized by companies seeking to establish operations in these two nations to formulate human resource management strategies that are both more efficient and better aligned with the specific local circumstances. Furthermore, the outcomes of this study can offer valuable insights for researchers and practitioners in the field of HR management who wish to gain a deeper understanding of these practices within the specific context of Southeast Asia